"Gay? Prove it": The politics of queer anti-deportation activism. (December 2014) - Lewis, Rachel A
This article examines how gender, sexuality, race and class intersect in queer asylum claims to influence the perceived credibility of gay and lesbian asylum applicants. Building on recent scholarship in queer migration studies that considers the role of gender and sexuality in the social construction of migrant illegality, this article explores how practices of credibility assessment in the political asylum process produce women and sexual minorities as deportable subjects. As I argue, the tactics utilized by gay male asylum applicants to resist deportation show how practices of credibility assessment in the political asylum process are linked to the state's reproduction of sexual citizenship narratives, narratives that have a disproportionately negative impact upon queer female migrants of color. Accounting for the intersections among gender, sexuality, race and class in influencing the perceived credibility of gay and lesbian asylum applicants is thus crucial for conceptualizing alternative forms of queer anti-deportation activism.